Prevalence and Recurrence Rates of Cytomegalovirus Infection Among Patients With Hematological Diseases in the Western Brazilian Amazon: A Cross-Sectional Study - de Melo Silva, Jean; Pinheiro-Silva, Renato; Costa de Oliveira, Regiane; de Castro Alves, Carlos Eduardo; Barbosa, Anderson Nogueira; Pontes, Gemilson Soares (Frontiers in Public Health, 2021)
Cytomegalovirus (CMV) is a worldwide distributed pathogen that may cause serious complications in patients with hematological diseases. This study aimed to serologically characterize the CMV infection in patients suffering from hematological diseases in Amazonas, Brazil. Serum samples from 323 patients were tested for the presence of anti-CMV IgM or IgG antibodies by an enzyme-linked immunosorbent assay. Positive samples for IgM were submitted to the IgG avidity test to differentiate primary infection from recurrent infection. An epidemiological questionnaire was administered to collect sociodemographic information of the study population. The overall prevalence of CMV infection verified in this study was 91.3%. The highest rates were found in patients suffering from platelet disorders (94.5%), anemia (93.3%), or leukemia (91%). The study population was predominantly composed of individuals with low socioeconomic status. Blood transfusions were more often in patients with anemia or leukemia, but it was not correlated with the positivity for CMV infection. Measurement of IgG avidity in patients positive for anti-CMV IgM demonstrated a recurrent infection rate of 5.2% (17/323). Over 80% of recurrent infections occurred in patients with acute lymphocytic leukemia (ALL) or anemia. Our findings indicated that CMV infection is highly prevalent in patients with hematological diseases from the Brazilian western Amazon. The prevalence observed progressively rose with increasing age, whereas anemia or ALL disease figured as risk factors for the recurrence of CMV infection.